2015
DOI: 10.1111/exd.12827
|View full text |Cite
|
Sign up to set email alerts
|

Hair growth‐promotion effects of different alternating current parameter settings are mediated by the activation of Wnt/β‐catenin and MAPK pathway

Abstract: Electrical stimulation is being used in variable skin therapeutic conditions. There have been clinical studies demonstrating the positive effect of electrical stimuli on hair regrowth. However, the underlying exact mechanism and optimal parameter settings are not clarified yet. To investigate the effects of different parameter settings of electrical stimuli on hair growth by examining changes in human dermal papilla cells (hDPCs) in vitro and by observing molecular changes in animal tissue. In vitro, cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…AKT, a downstream effector of phosphatidylinositol 3-kinase, is implicated in growth and survival of a variety of cells ( Hers et al, 2011 ). Activation of AKT appears to contribute to hair growth ( Sohn et al, 2015 ; Woo et al, 2017 ). Numerous studies have reported that EGCG regulates AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKT, a downstream effector of phosphatidylinositol 3-kinase, is implicated in growth and survival of a variety of cells ( Hers et al, 2011 ). Activation of AKT appears to contribute to hair growth ( Sohn et al, 2015 ; Woo et al, 2017 ). Numerous studies have reported that EGCG regulates AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The sonic hedgehog (Shh) and protein kinase B (AKT) signaling pathways are essential for the development and growth of hair follicles and transition between anagen and telogen ( St-Jacques et al, 1998 ; Wang et al, 2000 ; Sohn et al, 2015 ). Activation of the Shh or AKT signals can enhance the proliferation of hair follicle cells and promote hair growth ( Li et al, 2015 ; Lin et al, 2015 ; Sohn et al, 2015 ; Woo et al, 2017 ). EGCG has been demonstrated to trigger Shh signaling pathway in hippocampus of adult mice and enhance the hippocampal neurogenesis ( Wang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, electromagnetic field resulted in stimulation of DPCs activity . Electrical stimulation also induced hair regrowth by inducing hair follicular proliferation and stimulation of DPCs in vitro .…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%
“…MAP kinase-signaling pathway has been shown to be involved in the proliferation and migration of skin keratinocytes and fibroblasts [ 42 , 43 , 44 ]. To investigate the effects of visfatin on the activation of MAP kinases in HDFs, cells were treated with visfatin and phosphorylation of each MAP kinase was determined by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%